Germline Mutations of Inhibins in Early‐Onset Ovarian Epithelial Tumors. Issue 3 (27th December 2013) - Tournier, Isabelle; Marlin, Régine; Walton, Kelly; Charbonnier, Françoise; Coutant, Sophie; Théry, Jean‐Christophe; Charbonnier, Camille; Spurrell, Cailyn; Vezain, Myriam; Ippolito, Lorena; Bougeard, Gaëlle; Roman, Horace; et al.
<x xml:space="preserve">Abstract</x> Using the trio exome sequencing strategy, we identified a germline de novo mutation of the INHBA gene in a patient who developed sporadic bilateral ovarian epithelial adenocarcinomas at 21 years of age and showed that this mutation affects the inhibin/activin ratio. Identification in patients with early‐onset ovarian tumors of other variations affecting this gene or its partner INHA, functional assays and statistical tests indicate that germline alterations of the inhibin/activin pathway may contribute to the genetic determinism of early‐onset epithelial ovarian tumors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>